Formation of nickel-doped magnetite hollow nanospheres with high specific surface area and superior removal capability for organic molecules. (31st October 2016) - Li, Zhenhu; Ma, Yurong; Qi, Limin
Abstract: A strategy for the formation of magnetic Ni x Fe3− x O4 hollow nanospheres with very high specific surface areas was designed through a facile solvothermal method in mixed solvents of ethylene glycol and water in this work. The Ni/Fe ratios and the crystal phases of the Ni x Fe3− x O4 hollow nanocrystals can be readily tuned by changing the molar ratios of Ni to Fe in the precursors. An inside-out Ostwald ripening mechanism was proposed for the formation of uniform Ni x Fe3− x O4 hollow nanospheres. Moreover, the obtained Ni x Fe3− x O4 hollow nanospheres exhibited excellent adsorption capacity towards organic molecules such as Congo red in water. The maximum adsorption capacities of Ni x Fe3− x O4 hollow nanospheres for Congo red increase dramatically from 263 to 500 mg g −1 with the increase of the Ni contents ( x ) in Ni x Fe3− x O4 hollow nanospheres from 0.2 to 0.85. The synthesized Ni x Fe3− x O4 nanoparticles can be potentially applied for waste water treatment.